2020
DOI: 10.3390/met10050583
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pretreatment of Metal Glass Fe70Cr15B15 on Anodization in 1-butyl-3-methylimidazolium Tetrafluoroborate Ionic Liquid

Abstract: The impact of preliminary treatment (mechanical abrasion; chemical etching and anodization in ionic liquid) on the surface structure and corrosion behavior of Fe70Cr15B15 metal glass was studied. The detachment of the anodic oxide film from untreated Fe-amorphous alloy under anodization in ionic liquid was observed for the first time. The formation of hexagonal nanostructures (cells) on the surface of the Fe70Cr15B15 alloy after mechanical abrasion and following anodization in 1-butyl-3-methylimidazolium tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Titanium oxide nanotubes with a diameter of 30 to 45 nm were obtained. Water or propylene glycol was added to the solvent (ionic liquid) [143]. The Ti 4+ ions formed during the anodic dissolution of titanium in the presence of water form aqua complexes of the composition [Ti(H 2 O) 4 ] 4+ , which produced titanium oxide during hydrolysis.…”
Section: Nanomaterials Based On Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium oxide nanotubes with a diameter of 30 to 45 nm were obtained. Water or propylene glycol was added to the solvent (ionic liquid) [143]. The Ti 4+ ions formed during the anodic dissolution of titanium in the presence of water form aqua complexes of the composition [Ti(H 2 O) 4 ] 4+ , which produced titanium oxide during hydrolysis.…”
Section: Nanomaterials Based On Oxidesmentioning
confidence: 99%
“…Glycols and polyols are important additives in the synthesis of well-characterized nanostructured oxide materials, since they are chelating ligands with respect to metal ions, which allows the control of the rate of hydrolysis of transition metal alkoxides [145]. Glycolates of the composition Ti(OCH(CH 3 )CH 2 OH) 2+ are formed in situ [143]. Figure 6 shows a micrograph of a fragment of the surface of a titanium anode obtained when exposed to an anode current in the ionic liquid BMIMCl in the presence of a water additive in an air atmosphere at a temperature of 25 • C [143].…”
Section: Nanomaterials Based On Oxidesmentioning
confidence: 99%
“…A review [19] showed the role of an ionic liquid (IL) in the formation of nanostructures. Anodizing an alloy in an ionic liquid can lead to the formation of porous oxide, dense oxide film, the appearance of nanotubes, nanocells, nanorolls decorated with nanotubes, and many other forms [19][20][21][22]. The task of using the material determines the type of surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…The task of using the material determines the type of surface modification. It has been shown that the amorphous alloy Fe70Cr15B15 with a surface modified with hexagonal nanostructures demonstrates a significant anodic shift of the corrosion potential (E corr = + 379 mV) compared to the initial alloy (E corr = −125 mV) [20].…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of metal ions and metal oxides after pre-treatment is important [ 26 ]. The sample is pretreated before the electropolishing process, which removes passive layers and induces a rapid increase in activity and changes the surface properties [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%